A comprehensive study of the optical properties of emitting polymers for efficient flexible OLED devices. Issue 11 (16th September 2016) - Gioti, M.; Kokkinos, D.; Chaidou, C. I.; Laskarakis, A.; Andreopoulou, A. K.; Kallitsis, J. K.; Logothetidis, S.
Abstract : In this work, the fabrication and characterization of flexible organic light emitting diode (OLED) devices by printing processes is presented. New synthesized anthracene‐based polymer as well as commercially available polymers such as polyfluorenes and polyphenylene vinylenes were applied as emitting materials. The photoluminescence (PL) properties of the polymer films were evaluated revealing the characteristic emission of each material. The optical properties of the polymers were investigated by NIR‐Vis‐far UV spectroscopic ellipsometry. The accurate determination of the thickness and the optical properties were derived. Furthermore, electro‐optical characteristics brightness, chromaticity, and current density–voltage characteristics of the devices were obtained. Correlations between the optical properties, PL characteristics, and device performances were established. This provides substantial insights into the final design of the optimum final multi‐layer structure of the OLEDs whereas the potentiality for the development of flexible OLEDs with bigger active area devices by printing processes is demonstrated.